Implementasi Pembacaan Shalawat Nabi dalam Meningkatkan Nilai Spiritual Siswa di Sekolah - Siti Istiqomah; Alfa Nadia Mahira (Prodi Pendidikan Keagamaan Islam, 2024)
This research is motivated by the decline in students' moral attitudes in the context of increasingly advanced technology and many teenagers who are increasingly reciting shalawat. This study aims to explain how to improve the spiritual value of class VIII students of SMP Juara Pekanbaru. This type of research uses a qualitative approach and data sources are obtained through observation, interviews, and documentation from relevant sources. The data analysis techniques used in this study are data reduction, data presentation, and conclusion. From this study the author found just the increase in the spiritual value of reciting shalawat at SMP Juara Pekanbaru with the following steps: 1) da'wah method. 2) habits. 3) advice. 4) supervision. And there are also supporting factors from teachers and parents. With the habit of reciting shalawat at SMP Juara Pekanbaru, students gain peace of mind, increase obedience in worship, and increase enthusiasm. In addition, reciting shalawat can change their thinking and inspire them to behave well according to Islamic teachings. This can be shown through habits, understanding and role models to achieve the desired results.